Narrative, Film, and Identity : How Cinema Impacts the Meaning of Life - Pamerleau, William C., (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
Our identities are shaped by narratives, and cinema contributes to that process. While there is substantial scholarship on both narrative identity and film narrative, there is very little investigation of the intersection between them. This book provides that, with particular attention to how the interaction between film narratives and life narratives affect the meaning of life. Traditional issues like spectator activity and realism appear in a different light when viewed through this interaction. It also reveals how film can both help and hinder the meaning of our lives by sustaining oppressive narratives or promoting new narrative possibilities. See Less